Process-philosophical Perspectives on Biology: Intuiting Life (Edited by Spyridon A. Koutroufinis and Arthur Araujo)—Philosophical Intuitions for a New Understanding of Life - Bizzarri, Mariano (Organisms. Journal of Biological Sciences, 2023)
Book review